L’ Etiopia e il conflitto nel Tigrai - Sale, Giovanni (La civiltà cattolica, 2021)
The government in Addis Ababa continues to describe its actions in November 2020 against its rebel province of Tigrai, in the north of the country as a simple internal police operation. In reality, the clash between the Ethiopian Federal Army and the Tigray Popular Liberation Front was a full-blown civil war. The conflict has caused more than 1,000 deaths, including several hundred civilians, and about 50,000 refugees, who have crossed the border with Sudan, to escape possible reprisal actions. The war in Tigray threatens to implode Ethiopia, a poor country subject to periodic droughts, with almost 109 million inhabitants, 40% of whom are minors.